2019
DOI: 10.1071/rj19066
|View full text |Cite
|
Sign up to set email alerts
|

Optimising cattle grazing distribution on rangeland: a systematic review and network analysis

Abstract: Optimising beef cattle (Bos taurus and Bos indicus) distribution, both spatially and temporally, is one of the most significant challenges associated with managing extensive grazed rangelands. Landscape variability and behavioural patterns of cattle may lead to non-uniform and inefficient forage utilisation, damage to critical habitats, and water quality impairment. In order to overcome these distribution challenges, a large suite of tools have been developed and researched to optimise grazing patterns. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…In arid and semiarid shrublands, fine adjustments to animal numbers and practices that improve grazing distribution at local, regional, and landscape scales are likely needed to effectively maintain or improve fuel management and overall rangeland health. Supplementation (Stevenson et al this issue ), virtual fencing (Boyd et al this issue ), and modified timing of grazing (such as off-season use), along with other measures ( Creamer et al 2019 ), can help achieve desired fuel reductions. Grazing needs to be applied with care to ensure desired objectives are achieved and to prevent undesirable compositional shifts in plant communities, impacts to wildlife, or reductions in ecosystem functioning.…”
Section: Implications For Fire Management On Rangelandsmentioning
confidence: 99%
“…In arid and semiarid shrublands, fine adjustments to animal numbers and practices that improve grazing distribution at local, regional, and landscape scales are likely needed to effectively maintain or improve fuel management and overall rangeland health. Supplementation (Stevenson et al this issue ), virtual fencing (Boyd et al this issue ), and modified timing of grazing (such as off-season use), along with other measures ( Creamer et al 2019 ), can help achieve desired fuel reductions. Grazing needs to be applied with care to ensure desired objectives are achieved and to prevent undesirable compositional shifts in plant communities, impacts to wildlife, or reductions in ecosystem functioning.…”
Section: Implications For Fire Management On Rangelandsmentioning
confidence: 99%
“…There is immense value in studying human-animal interactions in rangeland cattle because they can provide insight for animal welfare and production [ 3 , 11 ], as well as how individual differences in behavior manifest in altering landscapes and biodiversity of surrounding ecosystems [ 133 , 134 , 135 , 136 ]. However, this value is at risk of being undermined by methods that do not take into account the unique characteristics of range cattle outlined above.…”
Section: Recommendations For Future Hai Research In Rangeland Cattmentioning
confidence: 99%
“…These are scenarios where livestock preferences and landscape elements create uneven use and resulting impacts across grazing units (e.g. Creamer et al 2019). In similar grazing units across the region, Freitas et al (2014) found that implementation of distributional improvements without reduced stocking rates resulted in restoration rates of riparian plant communities equal to rates observed on units with grazing removed.…”
Section: Discussionmentioning
confidence: 99%
“…Optimising the spatial and temporal distribution of free-ranging livestock across complex landscapes is a significant challenge facing managers in vast grazing areas (Malan et al 2018;Creamer et al 2019). Stocking rate (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation